Arylnaphthalene Lignans from Daphne acutiloba Rehd. - Cao, Jing-Li; Xue, Jing-Jiao; He, Shun-Qin; Yang, Guang-Yu; Hu, Qiu-Fen (Asian Journal of Chemistry, 2010)
A new arylnaphthalene lignan (daphnelignan B), together with three known one, were isolated from the leaf and steam of Daphne acutiloba Rehd. Their structures were determined by means of HRESIMS, extensive 1D and 2D NMR spectroscopic studies and chemical evidence. The anti-HIV-1 activity of daphnelignan B was also evaluated and it shows an anti-HIV-1 activity with a TI (Therapeutic Index) above 35.62.